Monthly intravenous maintenance treatment with ustekinumab regains clinical response in patients with Crohn’s disease who no longer respond to the drug when administered subcutaneously - Berta López-Sáez; Ariadna Altadill; Eduard Brunet-Mas; Belen Garcia-Sagué; Luigi Melcarne; Laura Patricia Llovet; Luis Enrique Frisancho; Anna Puy; Sergio Lario; Maria Jose Ramirez-Lazaro; Jorge Del Estal; Albert Villoria; et al. (Therapeutic Advances in Gastroenterology)
Background: Several studies have assessed the efficacy of re-induction and subcutaneous intensification of ustekinumab (UST) to regain clinical remission of inflammatory bowel disease (IBD). However, very few have evaluated the effectiveness of intravenous UST for this purpose. Objectives: The aims of the study were to evaluate the efficacy of high-dose intravenous UST (USTiv) for regaining remission in Crohn’s Disease (CD) and to assess the safety of the drug. Design: Observational, retrospective, single-center study. Methods: All patients who had received intravenous UST to regain remission until June 2023 were included. Clinical response was evaluated using the Harvey-Bradshaw Index. Drug survival was calculated using Kaplan–Meier curves. Results: Twenty-three patients (52% female, mean age 40.5 ± 13.9) with CD were included. Seven (30%) patients had an incomplete primary response to UST, while 16 (70%) presented a secondary loss of response. Clinical response rates for USTiv administered monthly were 17/23 (73.9%) at week 8, 14/23 (60.9%) at week 16, and 10/12 (83.3%) at 1 year. Clinical remission rates were 11/23 (47.8%), 9/23 (39.1%), and 8/12 (66.7%), respectively. Median drug survival was 15.3 ± 7.7 months. Two patients (8%) experienced recurrent mild respiratory infections. No patients discontinued USTiv due to adverse events. Conclusion: More than half of the patients with CD who underwent maintenance treatment with USTiv regained clinical response after failing with subcutaneous UST treatment. No significant adverse events were observed.